1980
DOI: 10.3758/bf03204258
|View full text |Cite
|
Sign up to set email alerts
|

Iconic memory and visible persistence

Abstract: There are three senses in which a visual stimulus may be said to persist psychologically for some time after its physical offset. First, neural activity in the visual system evoked by the stimulus may continue after stimulus offset ("neural persistence"). Second, the stimulus may continue to be visible for some time after its offset ("visible persistence"). Finally, information about visual properties of the stimulus may continue to be available to an observer for some time after stimulus offset ("informationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
719
6
4

Year Published

1984
1984
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 926 publications
(766 citation statements)
references
References 101 publications
37
719
6
4
Order By: Relevance
“…With only seven stimuli in each grid, and no masking stimulus, even the shortest stimulus duration (50 ms) was sufficient to produce a brief impression of a matrix .of letters. Such exposures typically produce correct immediate reports of a substantial number of letters when they are tested individually by location cuing (Sperling, 1960;Coltheart, 1980). Subjects in all groups were shown a sample grid and were told that they would be viewing a series of 4 × 4 grids containing symbols in different typefaces.…”
Section: Ljmentioning
confidence: 99%
“…With only seven stimuli in each grid, and no masking stimulus, even the shortest stimulus duration (50 ms) was sufficient to produce a brief impression of a matrix .of letters. Such exposures typically produce correct immediate reports of a substantial number of letters when they are tested individually by location cuing (Sperling, 1960;Coltheart, 1980). Subjects in all groups were shown a sample grid and were told that they would be viewing a series of 4 × 4 grids containing symbols in different typefaces.…”
Section: Ljmentioning
confidence: 99%
“…100 msec, it should appear to temporally overlap stimuli that follow in less than 100msec. Previous estimates of the duration of visible persistence based on this method range between 100 and 300msec (Coltheart, 1980). When the distance and time between successive stimuli approaches zero, as in the case of real motion, the duration of visible persistence can be estimated by the length of an object's blur streak.…”
Section: Introductionmentioning
confidence: 99%
“…I mentioned that earlier work (summarized in [2,10]) showed that iconic memory is not based in early vision, but, in light of these findings, one sees that the so-called 'iconic memory' that was the subject of those Sperling experiments was an amalgam of two different kinds of memory: a rod-based 'pure iconic' memory lasting at most a few hundred msec and a much longer-lived fragile VSTM that is based higher up in the visual system and lasts up to 4-5 seconds. Indeed, Sligte et al [9] found neuroimaging evidence of long lasting spatiotopic representations that correspond to fragile VSTM in visual area V4 but not in the lower areas V1, V2 or V3.…”
Section: Capacity Interstimulus Interval (Ms)mentioning
confidence: 99%
“…By relying on this form of memory, we isolate consciousness from the immediate feed of the world and the retina. The neural locus of the high memory capacity demonstrated in the Sperling phenomenon is in brain areas that are candidates for the neural basis of conscious perception rather than in the retina or early vision [2,[8][9][10], and so the Sperling phenomenon may reveal the capacity of conscious phenomenology.…”
mentioning
confidence: 99%